Task-Based Language Teaching (TBLT) Learning Model using Worksheets to improve Japanese writing skills - Wahani, Yenny Jeine (Vocational College of Diponegoro University, 2025)
This study aims to determine the effect of the application of Task-Based Language Teaching (TBLT) in the learning process of Goyou Bunseki course on Japanese language education students through semester V, Universitas Negeri Manado. This research is a class action research, data collection techniques in this research consist of tests and questionnaires. Based on the results, the application of Task-Based Language Teaching (TBLT) is proven to be effective in improving character learning outcomes in the Goyou Bunseki course of students. then Task-Based Language Teaching (TBLT) learning model can be used as an effective predictor in Japanese language learning and can be used as a guide for Japanese language teachers. This is also supported by student respondents in the questionnaire who agreed that Task-Based Language Teaching (TBLT) makes me have a responsible and disciplined character, learning activities using Task-Based Language Teaching (TBLT) have a positive impact.